ADVERBIAL MARKERS OF MODALITY IN NORWEGIAN L1 AND L2 CONVERSATIONS - Horbowicz, Paulina (Folia Scandinavica Posnaniensia, 2017)
The aim of this paper is to investigate how second language speakers of Norwegian (henceforth Norwegian L2 speakers) differ in their use of modality expressions from native speakers (L1 speakers). As modality is a very broad subject, the main focus of the study is limited to one-word modal adverbs, such as kanskje ‘maybe’, and modal particles such as jo. The study compares the frequency of using different types of modal adverbials by L1 and L2 speakers, and their syntactic position. The implications of the study are two-fold. First of all, it is to contribute to the studies of the field of modality in Norwegian. The second implication is didactic, as describing the use of modal adverbials in Norwegian conversation can help devise right teaching materials to allow second language users achieve a more native-like competence in this respect.